Natürliche und anthropogene Einflüsse auf den Hochwasserabfluß des Rheins - Bendix, Jörg (ERDKUNDE, 1997)
The investigation of daily discharges of the river Rhine since 1817 reveals a significant increase in frequency and intensity of severe flood events within the last twenty years. The goal of the current paper is to examine natural and human impacts which possibly are responsible for an intensification of the flood situation. Basically, severe flood events, especially at the Lower Rhine, have been proved to depend on natural climatic fluctuations and occur predominantly during periods of an intensified zonal circulation (west type) in winter which is linked to warm weather as well as persistent and heavy precipitation. Such weather situations could be mainly observed quasi-periodically during times of enhanced sunspot activity in combination with the Major Midwinter Warming (west type) of the arctic stratosphere, El Niño events and positive SST anomalies in the north-eastern Atlantic. Though not always independent of sunspot cycles, the current intensification of the flood water situation is accompanied by an merked increase in the persistence of the climatological situation described above. A combined use of general circulation models and a water balance model of the Rhine catchment point out that this intensification can be due to the man-made greenhouse effect. Based on a scenario with an increase in winter precipitation of 10% as could recently be observed within the Rhine catchment, the recurrence time of a century flood, as e. g. the event of 1993, would decrease to 40 years. Channel adjustment mainly aggravates the flood situation within the Upper Rhine area by means of an increase in wave velocity and the resultant coupling of the Rhine wave with flood waves of the mean tributaries, but has only small effects on the flood regime of the Lower Rhine. At the Bonn gauging station, even the use of future projected retention measures had lead to a reduction of the water-level during the century flood in 1993 of only 9 cm. The sensitivity of the flood regime of the river Rhine towards extensive land use changes seems to be low. After the results of a GIS-based water-balance model, a conversion of 25% farmland to coniferous forest within the Rhine catchment would only yield a water-level reduction of 6 cm at the Cologne gauging station. However, the impact of land use changes on the flood situation within large catchments is not yet fully understood and therefore, will need attention in future.